Dectetion of Verticillium dahliae kleb from olives trees with chronisc decline and dieback of branches and shoots - Gouveia, Maria Eugénia (2014)
Verticillium wilt of olive (Olea europaea L.) is economically important in all the Mediterranean region. Verticillium wilt of olive was first described by Ruggiere (1946) in Italy and after wards reported from all regions of olive cultivations. Recently had a great increasing particularly in newly established olive orchards (Mercado-Blanco et al, 2002). Verticillium dahliae Kleb. is a soil-born pathogen of several important commercial crops affecting vegetables, fruits, flowers and various woody ornamentals. Symptoms in olive trees appears chronically or they may be acute. Characteristics of chronic symptoms include small growth, dieback of shoots and branches and partial defoliation. In Portugal Verticillium wilt has not been considered an important disease and few studies were carried out about this disease. Recently an increasing number of cases of chronic decline, slow growth and defoliation have been reported in all regions where extensive plantations of olive orchards had occurred. Some of this cases are studied for diagnostic purpose.